Impact of Sunflower Cultivation on Livelihood Outcomes among Smallholder Farmers in Iramba District, Tanzania - Mchopa, Alban Dismas; Jeckoniah, John Nshimba (Advances in Social Sciences Research Journal, 2018)
Sunflower is among the cash crops with potentials for improving smallholder farmers’ livelihood. However, its impact on livelihood outcomes among smallholder farmers is hardly ascertained. The study specifically aimed to examine the contribution of sunflower cultivation on livelihood outcomes of smallholder farmers’ households basing on propensity scores matching. Cross-sectional research design was adopted whereby household survey, focus group discussion and key informant interviews were used to collect data. The study had a sample size of 368 respondents including sunflower and non-sunflower smallholder farmers. Qualitative data were transcribed, categorised, coded, thereafter grouped into themes and analysed using constant comparison technique. Quantitative data were analysed by using propensity score matching. Through propensity score matching, average treatment of the treated, difference in difference analysis, nearest neighbour matching and radius calliper matching techniques were used to establish the contribution. Findings indicate that participation into sunflower cultivation had an impact on livelihood outcomes as observed by the significant differences in livelihood outcomes (MD = 2.31; t = 5.94 from nearest neighbour matching and MD = 2.52; t = 9.69 from radius calliper matching). Therefore, the study concludes that sunflower cultivation had a significant impact on the livelihood outcomes among households of sunflower smallholder farmers. Thus, the null hypothesis was subsequently rejected. The study recommends to smallholder farmers that they should up-scale their production systems and techniques. This can be done through creating awareness and sensitisation on improved cultivation techniques that would guarantee more yields and household incomes for sustenance of the achieved livelihood outcomes.